Test-retest reliability of fitness and skill tests in elite male youth basketball players - Peters, D. M.; Balciunas, M.; Stonkus, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
To assess reliability of fitness and skill tests in elite youth basketball. Players (n=368) from 8 teams in Lithuania (U17 n=25; U16 n=21; U15 n=39; U14 n=57; U13 n=57; U12 n=37; U11 n=70; U10 n=58) completed 2 trials of 4 fitness tests: 20 metre sprint (Sprint); countermovement standing vertical jump (CMJ); standing vertical jump from squat (SVJ); side-step (SST) and two skill tests: ball dribbling (BD); & jump shot (JST), according to Balciunas et al., (2006). Change in mean & 95% confidence intervals, intra-class correlation coefficient, and log-transformed coefficient of variation were calculated (Hopkins, 2000) and correlated with age group. Results: Sprint: Cohort decrease in performance (mean diff .03secs, p<.001, 95% CI .04 & .01, ICCr .92, CV% 2.1); decrease for U17 (mean diff .04secs, p<.05, 95% CI .01 & .08, ICCr .74, CV% 1.9) and U10 (mean diff .06secs, p<.05, 95% CI .11 & .01, ICCr .71, CV% 3.2); ICCr range .71 to .89, CV% range 1.9 to 3.2 across years. CMJ: No cohort difference (mean diff .18cm, 95% IC .61 & -.26, ICCr .87, CV% 11.9) or year groups (mean diff range -.79 to .74cm, ICCr range .46 to .79, CV% 4.2 to 16.5); correlation between increasing age group and CV% (rho -.79, p<.05). SVJ: No cohort difference (mean diff .33cm, 95% CI .71 & -.04, ICCr .86, CV% 11.7); decreased performance for U16 (mean diff -1.44cm, 95% CI -1.6 & -2.73, p<.05, ICCr .70, CV% 6.1) and increased performance for U13 (mean diff .63cm, 95% CI 1.25 & .0, p<.05, ICCr .85, CV% 6.1) and U11 (mean diff 1.13cm, 95% CI 2.08 & .19, p<.05, ICCr .71, CV% 14.1); ICCr range .50 to .85, CV% range 4.7 to 15. SST: Cohort improvement (mean diff -.27secs, 95% CI -.21 & -.33, p<.001, ICCr .87, CV% 4.9) and all year groups (mean diff range -.15 to -.45secs, p<.05 to p<.001, ICCr range .72 to .90, CV% range 3.2 to 5.3) except U11; correlation between increasing age group and CV% (rho -.83, p<.05). BD: Cohort improvement (mean diff -.23secs, 95% CI -.17 & -.29, p<.001, ICCr .83, CV% 5.6) and all year groups (mean diff range -.19 to -.34, p<.05 to p<.001, ICCr range .62 to .91, CV% range 2.2 to 5.2) except U13. JSP: Cohort improvement (mean diff .72pts, 95% CI 1.04 & .41, p<.001, ICCr .45, CV% 54.5), with unacceptable ICCr (-.04 to .65) and CV% (28.5 to 77.1) ranges also in each age group. Conclusions: Cohort testretest differences were deemed `practically` unimportant with acceptable ICCr (>.70) except for JSP (ICCr .45). Trends for reduced CV% with increased age group reached statistical significance for the CMJ and SST suggesting increased variability in younger players. Apart from JSP, all tests are reliable for use with elite male youth players.